Tantangan Mekanisme Non-Conviction Based Asset Forfeiture dalam Rancangan Undang-Undang Perampasan Aset di Indonesia - Ilma, Hutmi Amivia (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: The recovery of assets and proceeds of crime has become an urgent global issue. International commitments, such as those enshrined in the United Nations Convention Against Corruption (UNCAC), encourage countries to actively pursue illegally acquired assets. The Asset Forfeiture Draft Bill is currently being drafted and is expected to strengthen Indonesia's efforts to fulfill this international obligation. This article discusses the challenges of the Non-Conviction Based Asset Forfeiture mechanism in the Asset Forfeiture Draft Bill in Indonesia. This research is normative research that analyzes the Asset Forfeiture Draft Bill and various relevant legal literature. Data collection is carried out through literature studies and analyzed qualitatively to describe the research object. The result of this study is that the Asset Forfeiture Draft Bill reveals a number of obstacles, including potential human rights violations, a shift in the paradigm of law enforcement, and a lack of coordination between institutions. However, given the limited effectiveness of imprisonment and fines in eradicating crime, the passage of this draft bill has become increasingly urgent to strengthen law enforcement and recover state losses. Keywords: Asset Forfeiture, Non-Conviction Based Asset Forfeiture, Corruption Crime, Draft Bill. Abstrak: Pemulihan aset hasil kejahatan telah menjadi isu global yang mendesak. Komitmen internasional, seperti yang tertuang dalam Konvensi PBB Anti Korupsi (UNCAC), mendorong negara-negara untuk secara aktif mengejar aset-aset yang diperoleh secara ilegal. Rancangan Undang-Undang Perampasan Aset yang tengah digodok diharapkan dapat memperkuat upaya Indonesia dalam memenuhi kewajiban internasional ini. Artikel ini membahas tentang tantangan mekanisme Non-Conviction Based Asset Forfeiture dalam Rancangan Undang-Undang Perampasan Aset di Indonesia. Penelitian ini adalah penelitian normatif dengan menganalisis RUU Perampasan Aset serta berbagai literatur hukum yang relevan. Pengumpulan data dilakukan dengan melalui studi pustaka dan dianalisa secara kualitatif untuk mendeskripsikan objek penelitian. Hasil penelitian ini adalah RUU Perampasan Aset mengungkap sejumlah kendala di antaranya adanya potensi pelanggaran hak asasi manusia, pergeseran paradigma penegakan hukum, dan kurangnya koordinasi antar lembaga. Meskipun demikian, mengingat keterbatasan efektivitas pidana penjara dan denda dalam memberantas kejahatan, pengesahan RUU ini menjadi semakin mendesak untuk memperkuat penegakan hukum dan memulihkan kerugian negara.